How terrorism ends: the impact of lethality of terrorist groups on their longevity - Nawaz, Muhammad Asif (Kansas State University, 2017)
This dissertation research examines the effect of organizational lethality on the longevity of terrorist groups. The current scholarship has sought to understand the demise of terrorist groups through means such as group success, government repression, negotiations, internal conflict, reorientation of goals, defeat, leadership decapitation and loss of public support. However, little research is available on the determinants of terrorists’ target selection and its implications for the group’s longevity. This study evaluates the targeting patterns and preferences of 480 terrorist groups that were operational between 1980 and 2011 and disaggre- gates the victims of all terrorist attacks into combatant versus non-combatant target-types. It is hypothesized that organizational lethality – defined as the average number of civilian killings generated by each group in its home-base country – is associated with negative group reputation, which results in faster group mortality. Popular support for violence, however, can influence and result from terrorism at the same time and has been found to be inherently endogenous by many previous studies. Therefore, a Seemingly Unrelated Bivariate Probit Model is employed to examine this endogenous relationship, and the results confirm that there is a significant correlation between negative group reputation and group mortality. Moreover, the study differentiates between terrorist group activity – defined as average at- tacks generated by a group – and group lethality, and employs the Cox Proportional Hazard Model to estimate group duration. The study includes covariates like group size, ideology, positive consistency reputation and other factors affecting group longevity and mortality. The results imply that organizational lethality is associated with higher political risks for terrorist groups and tends to backfire by decreasing their survival probability. However, on the other hand, the study finds that an escalation in terrorist activity (launching more attacks) significantly increase the group longevity over time. The results of this study are tested by conducting group-specific case studies on the Afghan and Pakistani Taliban in Pak- istan using information collected from the English language Pakistani newspaper archives, and Harmony Database from Combat Terrorism Center at West Point, NY.
Keywords: Terrorist groups; Longevity; Target selection